2010
DOI: 10.1038/nchem.722
|View full text |Cite
|
Sign up to set email alerts
|

Electrically induced bonding of DNA to gold

Abstract: The development of single-molecule techniques has afforded many new methods for the observation and assembly of supramolecular structures and biomolecular networks. We previously reported a method, known as the single-molecule cut-and-paste approach, to pick up and deposit individual DNA strands on a surface. This, however, required pre-functionalization of the surface with DNA strands complementary to those that were to be picked up and then deposited. Here we show that single molecules of double-stranded DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…The polymer is also given an increased chance to experience large friction against the electrophoretic driving force via the electrically-induced Au electrode-DNA interactions20272829. This transverse field induced resistance overwhelms the anionic electroosmotic dragging considering the strong nonspecific affinity of DNA to Au1127282930 as well as the electrostatic interaction between the DNA and the positively charged electrode, and causes the orders of magnitude decrease in the translocation velocity. On the other hand, the spatially confined trapping field allows large number of polynucleotide chains to electrophoretically flow at center of the nanochannel (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The polymer is also given an increased chance to experience large friction against the electrophoretic driving force via the electrically-induced Au electrode-DNA interactions20272829. This transverse field induced resistance overwhelms the anionic electroosmotic dragging considering the strong nonspecific affinity of DNA to Au1127282930 as well as the electrostatic interaction between the DNA and the positively charged electrode, and causes the orders of magnitude decrease in the translocation velocity. On the other hand, the spatially confined trapping field allows large number of polynucleotide chains to electrophoretically flow at center of the nanochannel (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ECAFM has, however, offered new perspectives in two recent reports. One study by Gaub and coworkers 30,31 has shown the feasibility of direct measurement of electrically induced nitrogen-gold bonding via the interaction of DNA fragments with a gold substrate. Another report has demonstrated that significant structural changes of a metalloenzyme can be detected when the enzyme is electrochemically brought from its resting state to its catalytically active state 26 .…”
mentioning
confidence: 99%
“…Another favored substrate is gold because of the ease of preparation and the well‐characterized nature of the chemistry associated with self‐assembly on the surface. Moreover, its high conductivity allows for the combination of force spectroscopy and electrical measurements . Molecules can be directly immobilized on gold surfaces through thiol groups, although thiol–gold bonds are known to be relatively weak and mobile …”
Section: Immobilization Of Molecules For Force Spectroscopymentioning
confidence: 99%